STEAM-ing: preliminary insights in consolidating arts with STEM / Siti Soraya Ramli ... [et al.] - Ramli, Siti Soraya; Maaruf, Siti Zuraida; Mohamad, Syamsul Nor Azlan; Abdullah, Nabilah; Md Shamsudin, Nurshamshida; Syed Aris, Sharipah Ruzaina (Universiti Teknologi MARA, 2022)
Science, mathematics, technology, and engineering (STEM) have long been acknowledged as subjects that are fundamental for national progress and growth. Efforts to integrate the “arts” component in the teaching and learning of STEM subjects have begun over two decades ago through the introduction of KBSR and KBSM in the Malaysian school curriculum; however, its implementation received mixed reactions. The reason is that although “art” can and does make STEM subjects interesting and engaging, it could also distract and remove the focus away from STEM components. Realizing the importance of Arts in complementing the learning of science-based subjects in terms of creativity and collaborative focus, this study aims to uncover the views schoolteachers encounter as they try to integrate Arts in STEM teaching. Using a qualitative approach, the study involved teachers currently teaching STEM subjects in local public and private schools. Data was collected via a semistructured interview with four experienced Science teachers. Findings revealed all Science teachers unanimously agree the integration of Visual Arts elements in STEM could ease various pedagogical challenges which include students’ thinking ability, practical knowledge, and ability in technology; constraints related to teaching aid and ensuring student understanding of “difficult” topics in the lower secondary Science syllabus.